ANALYSIS OF SUCCESSFUL IMPLEMENTATION OF ORDER TO MEASUREMENT MARKET POLICY IN SUKODONO PEOPLE'S MARKET, SIDOARJO REGENCY (Universitas 17 Agustus 1945 Surabaya, 2021)
The Minister of Trade of the Republic of Indonesia explained that the revitalization of the market contains two important elements, namely the implementation of the physical development of the market, and the arrangement of the system including the certainty of the delivery of the quantity of goods or services. Guarantee of correctness in the use of measuring instruments, particularly in trade transactions, will play an important role in supporting macroeconomic growth .Therefore, it is important to activate the Orderly Measurement Market in every Regency/City area in Indonesia. One of the markets that received an award as an Orderly Measurement Market is the Sukodono People's Market in Sidoarjo Regency. The success of the implementation of the Orderly Measures Market Policy in the Sukodono People's Market was investigated using a qualitative descriptive method. The theory of policy implementation used in this research is the theory of Van Meter and Van Horn . Data mining was carried out by in-depth interviews with relevant stakeholders . The results showed that fThe main actors in the successful implementation of the Orderly Measuring Market policy in the Sukodono People's Market are Policy Standards and Targets, Financial/financial Resources, Inter-Organizational Communication and Strengthening Activities, Characteristics of Implementing Agents, and Implementor's Disposition.